532 CARING FOR AND CARING ABOUT OLDER PEOPLE LIVING WITH SEVERE FRAILTY DURING COVID-19. (14th June 2021) - Green, R; King, H; Nicholson, C
Abstract: Introduction: An ongoing study collected survey and interview data from older people with frailty living in the community near end-of-life during the Covid-19 pandemic. Methods: Unstructured interviews with older people with frailty living in the community (N = 10), which included accounts from unpaid carers (N = 5), were video and audio recorded between October–November 2021. Six of these older people have died since fieldwork completion. A face-to-face survey collected data from a further 10 older people. Participants ages ranged from 70–99, 11, men, and 9 women, living in owned, rented, or sheltered accommodation, with Clinical Frailty Scores of 6 (N = 8), 7 (N = 9), and 8 (N = 3). Results: Topics raised in relation to the pandemic included loss of social contact and increased loneliness, concern about not physically getting out, and losing physical function. Older people struggled to gain access to health and social care for support and previously received services were withdrawn. Most participants did not have access to internet and relied heavily on families to facilitate virtual contact with health professionals. Families and friends were the main anchor in facilitating social and health care including chasing up medications, liaising with social care to ensure quality and consistency of care provided, and monitoring older people's health. Where older people's conditions worsened family provided intense support, though family carers described the strain and unsustainability of this provision. Older people and their families felt they had been forgotten. Conclusions: These are insights from hard-to-reach population that are frequently invisible. Greater examination of the impact of using communication technologies in care provision on those with poor access to and capabilities with using these technologies is required. Unpaid carers need more information and resources to support the care they provide and to facilitate access to appropriate social and health care services for those they care for.